Policy Model of Physical Changes in The Environment of Mandeh Area from 2008-2018 - Syam, Alexander (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
ABSTRACT The purpose of this study was to see the physical changes in the environment of Mandeh area, South Pesisir Regency, from 2008-2018 and formulate an environmental policy model for the Mandeh area. The analysis technique was carried out by overlaying map of Mandeh area land use from 2008-2018, to determine the policy model of the physical changes in the environment of Mandeh area was analyzed by FGD and AHP. As for the results of the land use map overlay shows many physical changes. Based on the results of the analysis and discussions that have been done previously, it can be concluded that Physical Changes in Enviroment of Mandeh area from 2008-2018 have their own impact on the environment For this reason, it is necessary to have an environmentally sound policy model. Based on the results of the analysis, there are five alternative policy priorities are: (1) it is expected that the government to analyze the utilization of natural resources does not exceed the environmental carrying capacity value of 0.752, (2) zoning of land use and marine waters of mandeh area value 0.791 (3) cultivating the main functions of natural resources potential, human resources and artificial resources value 0.794 (4) conservation for mangroves and coral reefs that have been damaged value 0.732 (5) analysis of the system plan and road network of sea and land transportation value 0.726. Keywords: Environmental Physical Changes, Mandeh Region